EFEKTIVITAS KEBIJAKAN PEMERINTAH MENGENAI WAJIB BELAJAR 9 TAHUN SECARA GRATIS BAGI KAUM PROLETAR DI DUSUN BORAH KECAMATAN PUJON KABUPATEN MALANG - Nikmatul Ma’rifah, Nila Wahyuningsih (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2011)
Government policy regarding the 9-year compulsory education is a policy that made the government to improve the quality of resources in Indonesia. This policy on the designation for all levels of Indonesian society, but particularly aimed at the middle to lower economic (the proletariat), where communities are living in remote areas with medium-economic conditions. But they also deserve the same education that is listed in UUSPN No. 20 of 2003, chapters 5 and 6. According to researchers from the results of research on the effectiveness of government policies regarding the 9-year compulsory education free of charge to the proletariat at Hamlet Village Borah WiyurejoPujon district can be concluded that the policy can be effective, because according to the results of research interviews with informants that government policies regarding the compulsory 9 year for free is already running and is evidenced by payment of tuition fee waiver, building fees and cutting the price of the book. But also there are still costs in the collection by institutions such as the cost of making rapot and costs to the national final exams. Many benefits are felt by Hamlet Borah with the policy of this government that waivers of school fees and many children who were not initially school because parents can not afford to be interested in school. Advisor: Dr. H. Nur Ali, M.PdKey words: Effectiveness, Government policy for 9-yearcompulsory education, the Proletariat.